PELATIHAN DEEP LEARNING BAGI GURU SLB: LANGKAH MENUJU PENDIDIKAN BERBASIS TEKNOLOGI ASISTIF DAN PEMBELAJARAN ADAPTIF - Jauhari, Muhammad Nurrohman; Ana Rafikayati; Amelia Rizky Idhartono; Nurul Hidayati; Riski Prasetya Arbi; Aulia Dwi Shanty (Universitas PGRI Adi Buana Surabaya, 2025)
The implementation of this community service program aimed to provide knowledge on deep learning based on assistive technology and adaptive learning. The methods of implementation included (a) planning, (b) implementation, and (c) evaluation. Based on the results of the program, it can be concluded that the success in increasing participants' knowledge about the training on deep learning for teachers as a step toward education based on assistive technology and adaptive learning has had a positive impact on teachers. This success is reflected in the improvement of participants' average pre-test scores, which increased from 50.26 to an average post-test score of 78.21.